Optical properties of CSS/GPS sources. Issue Volume 15:Issue S359(2020) (March 2019) - Nascimento, Raquel S.; Rodríguez-Ardila, Alberto; Faria, Marcos F.; Marinello, Murilo; Dahmer-Hahn, Luis G.
Abstract: In this work, we study the optical properties of 58 CSS/GPS radio sources selected from the literature in order to determine the impact of the radio-jet in the circumnuclear environment of these objects. We obtained optical spectra for all sources from SDSS-DR12 and performed a stellar population synthesis using the Starlight code. Our results indicate that the sample is dominated by intermediate to old stellar populations and there is no strong correlation between optical and radio properties of these sources.